2011
DOI: 10.1111/j.1440-1800.2011.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Valued identities and deficit identities: Wellness Recovery Action Planning and self-management in mental health

Abstract: Wellness Recovery Action Planning (WRAP) is a self-management programme for people with mental illnesses developed by a mental health consumer, and rooted in the values of the 'recovery' movement. The WRAP is noteworthy for its construction of a health identity which is individualised, responsibilized, and grounded in an 'at risk' subjectivity; success with this programme requires development of an intensely focused health lifestyle. We draw on Bourdieu and Giddens to argue that what is being developed is a 'r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
0
25
0
6
Order By: Relevance
“…The contrast between the managed patient and the ideal patient as an autonomous, reflexive and active consumer of health care creates a tension for mental health services and those they serve. Neoliberal discourses position the ideal health consumer as someone who takes responsibility for the maintenance of their own health rather than depending on professionals for this . Workers and patients may however have alternative and competing normative versions of what it means to be a mental health patient .…”
Section: Discussionmentioning
confidence: 99%
“…The contrast between the managed patient and the ideal patient as an autonomous, reflexive and active consumer of health care creates a tension for mental health services and those they serve. Neoliberal discourses position the ideal health consumer as someone who takes responsibility for the maintenance of their own health rather than depending on professionals for this . Workers and patients may however have alternative and competing normative versions of what it means to be a mental health patient .…”
Section: Discussionmentioning
confidence: 99%
“…The underpinning of these approaches is the philosophical commitment to attending to human capacity first rather than human deficiency (Scott & Wilson, 2011). It assumes that every person can build a meaningful and satisfying life defined by an individual's own terms .…”
Section: Introductionmentioning
confidence: 99%
“…In their attempt, an exhaustive review was conducted for literature in psychology, philosophy and social work, and 24 character strengths (e.g., creativity, persistence, social intelligence and hope) were subsequently identified that are considered to underpin our universal Across the range of strengths-based approaches to mental health care, there is a focus on inter-personal processes working with the strengths of the individual and their community to achieve client-defined goals and personal recovery (Slade, 2009;SmithMerry, Freeman, & Sturdy, 2011). The underpinning of these approaches is the philosophical commitment to attending to human capacity first rather than human deficiency (Scott & Wilson, 2011). It assumes that every person can build a meaningful and satisfying life defined by an individual's own terms 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the construction of identity in the contemporary world occurs within vast intertwining arenas of insecurity, in which life is bound to the dynamics of a globalized capitalist economy and interconnected with an institutionalised and permanent risk environment, living and surviving in this conjuncture enables it to be mutable, flexible and adaptable 5,6 .…”
Section: Comunicação Saúde Educação 2015; 19(54):479-90mentioning
confidence: 99%
“…The discovery of identity depends on the person and the negotiations he or she undertakes with others occurring at any given moment and in any given context 2,3 . It is metamorphosis and is historically constituted, since the human being, full of possibilities, constantly (re)constructs him or herself throughout the course of his or her life and is both protagonist and author of his or her own history 4 . Thus, although the construction of identity in the contemporary world occurs within vast intertwining arenas of insecurity, in which life is bound to the dynamics of a globalized capitalist economy and interconnected with an institutionalised and permanent risk environment, living and surviving in this conjuncture enables it to be mutable, flexible and adaptable 5,6 .…”
Section: Introductionmentioning
confidence: 99%